Breaking Barriers: A New Era in Arabic Language Learning Through Digital Platforms - Setiadi, Fadlan Masykura (Journal of Arabic Education and Linguistics, 2025)
This study explored the transformative potential of digital platforms in Arabic language learning, particularly focusing on how these technologies break traditional barriers to Arabic language acquisition. This research employed qualitative research with a type of literature study. The primary sources of data for this study's data on the integration of digital platforms in Arabic language learning were a number of books, journals, websites, and other literary works. Meanwhile, data analysis techniques used the Miles and Huberman model, namely data collection, data reduction, data display, and data verification. The findings showed that the educational paradigm in Arabic language learning has undergone significant shifts towards technology integration. This study also concludes that digital platforms have great potential to break down traditional barriers in Arabic language learning, especially regarding the limitations of conventional classrooms and materials, thereby paving the way for a new era of learning that is more inclusive and accessible.